1996
DOI: 10.1093/oxfordjournals.annonc.a010718
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of cyclin D1 expression in patients with node-positive breast carcinoma treated with adjuvant therapy

Abstract: The patients with node-positive breast cancer who have a higher likelihood of gaining benefit from adjuvant therapy are those with tumours with cyclin D1 nuclear expression, small size and less than 3 metastatic nodes. Further studies are needed to verify the prognostic value of cyclin D1 in relation to different adjuvant treatments and to deepen the biological pathways that regulate its activation/ suppression in human breast carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
23
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 26 publications
8
23
0
1
Order By: Relevance
“…13,14 After several attempts at optimising mouse monoclonal and rabbit polyclonal antibodies to cyclin D1, we have attained reproducible results with the rabbit monoclonal antibody employing the protocol described by Cheuk et al 28 In contrast to other antibodies, the new rabbit anticyclin D1 monoclonal antibody shows a strong correlation with CCND1 gene amplification. However, in accordance with previous studies, 1,11,13,14,16,[19][20][21] cyclin D1 overexpression was still more pervasive than gene amplification. In the present study, 67.4% of the cases showed strong cyclin D1 expression, whereas only 11.6% showed very low levels or no expression of this cell cycle regulator.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…13,14 After several attempts at optimising mouse monoclonal and rabbit polyclonal antibodies to cyclin D1, we have attained reproducible results with the rabbit monoclonal antibody employing the protocol described by Cheuk et al 28 In contrast to other antibodies, the new rabbit anticyclin D1 monoclonal antibody shows a strong correlation with CCND1 gene amplification. However, in accordance with previous studies, 1,11,13,14,16,[19][20][21] cyclin D1 overexpression was still more pervasive than gene amplification. In the present study, 67.4% of the cases showed strong cyclin D1 expression, whereas only 11.6% showed very low levels or no expression of this cell cycle regulator.…”
Section: Discussionsupporting
confidence: 88%
“…Conflicting results on the prognostic impact of cyclin D1 overexpression and clinical outcome in breast cancer patients have been reported. 1,11,[16][17][18][19][20][21][37][38][39] Despite the known problems with commercially available anticyclin D1 antibodies, a considerable amount of data linking cyclin D1 overexpression with lack of response to tamoxifen have been published. 13,14 After several attempts at optimising mouse monoclonal and rabbit polyclonal antibodies to cyclin D1, we have attained reproducible results with the rabbit monoclonal antibody employing the protocol described by Cheuk et al 28 In contrast to other antibodies, the new rabbit anticyclin D1 monoclonal antibody shows a strong correlation with CCND1 gene amplification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we think of multiple, preneoplastic epithelial areas scattered throughout the organ, then the data could be interpreted to suggest that lesions with overexpression of cyclin Dl are less likely to progress to full malignancy. This surprising idea arose in part from the consideration of four separate studies, in which overexpression of CCNDI in tumours appeared to be associated with a less aggressive phenotype or was a favourable prognostic indicator (Betticher et al, 1996;Bringuier et al, 1996;Gillett et al, 1996;Pelosio et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The present study however, highlights the need to further evaluate the relationship between cyclin D1 expression and prognosis given that ampliĀ®cation is a poor surrogate for overexpression. The Ā®ve studies reported to date have failed to reach a consensus: two reported an improved relapse-free and overall survival in the patients with cyclin D1 overexpressing tumours (Gillett et al, 1996;Pelosio et al, 1996), whereas the other studies failed to identify any impact of cyclin D1 expression on survival (McIntosh et al, 1995;Michalides et al, 1996;van Diest et al, 1997). Further studies are therefore required to elucidate the prognostic signiĀ®cance of cyclin D1 and EMS1 overexpression.…”
mentioning
confidence: 99%